The Asymptomatic Carotid Surgery Trial 2: Background and aims of the ACST-2 study. - Halliday, A; Macdonald, S (Bryn Mawr Communications II, 2012)
The Asymptomatic Carotid Surgery Trial 2 (ACST-2) seeks to compare carotid artery stenting (CAS) and carotid endarterectomy (CEA). A 1:1 randomization construct is used for suitable patients with an asymptomatic carotid stenosis that is considered to warrant revascularization, in whom CAS or CEA are equally applicable, and when there is substantial uncertainty regarding which method of intervention is preferred. All patients recruited into the trial are on the contemporary best medical therapy. The recruitment target is 5,000 patients. The ACST-2 trialists consider that large, “simple” trials such as this are likely able to yield meaningful and generalizable results and lend themselves to valid subset analyses at completion. Furthermore, contemporary procedural all stroke/death rates for carotid intervention (taken from REST) are < 3%, and any robust comparison of the two treatment arms will require a sizeable trial population. Basing eligibility on uncertainty should ensure the large-scale recruitment of an appropriately heterogeneous group. This increases the value of the study, perhaps making it possible to determine whether the net effects of CEA/CAS are influenced by certain patient characteristics recorded at enrollment.